1996
DOI: 10.1210/mend.10.10.9121486
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of promoter-specific activity by glucocorticoid receptor.

Abstract: Glucocorticoid receptor (GR) is expressed at essentially equal levels in almost all tissues and cell types. Remarkably, glucocorticoids themselves regulate transcription in vivo in both a promoter- and tissue-specific manner. Thus, specific systems must be in place to regulate receptor action within certain cells and at certain promoters. To address two specific aspects of these systems, we have analyzed promoter-specific activity of GR using two different, well studied promoters (termed simple and composite p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…[33][34][35]. For example, studies by Lefstin and Yamamoto included a variety of positive GREs and suggested that REs may act as "ligands for regulators" (34).…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35]. For example, studies by Lefstin and Yamamoto included a variety of positive GREs and suggested that REs may act as "ligands for regulators" (34).…”
Section: Discussionmentioning
confidence: 99%
“…Although GR alone has low affinity for sites that diverge from the GRE consensus, high affinity binding and transcriptional activation can be restored in the presence of multiple sub-optimal GR binding sites such as half GREs (Lechner et al, 1997) or adjacent binding sites for other transcription factors (Guido et al, 1996;Morin et al, 2000;Stafford et al, 2001;Strahle et al, 1988). Recruitment to such sites is thought to be mediated by both protein-DNA interactions and protein-protein interactions of GR with other transcription factors.…”
Section: Introductionmentioning
confidence: 99%
“…The agonist dexamethasone enhances GR-DNA binding severalfold, whereas antagonists including RU486 have no effect on GR-DNA binding. However, this observation is contested by a report that also implements gelshift methods with a palindromic GRE substrate but uses in vitro transcribed GR (13). This work shows that dexamethasone and RU486 predominantly affect the mobility of GR-DNA complex in a gel and only modestly affect the affinity of GR for DNA (13).…”
mentioning
confidence: 99%
“…However, this observation is contested by a report that also implements gelshift methods with a palindromic GRE substrate but uses in vitro transcribed GR (13). This work shows that dexamethasone and RU486 predominantly affect the mobility of GR-DNA complex in a gel and only modestly affect the affinity of GR for DNA (13). Therefore, although ligands clearly regulate GRmediated transcriptional activity, a direct effect of these ligands on specific GR-DNA interactions is controversial.…”
mentioning
confidence: 99%
See 1 more Smart Citation